Evolution of the universe driven by a mass-dimension-one fermion field - Pereira, S. H. [UNESP]; Holanda, R. F.L.; Souza, A. Pinho S. [UNESP] (IOP Publishing, 2017)
This paper studies the evolution of the universe filled with a neutral mass-dimension-one fermionic field, sometimes called Elko. The numerical analysis of the coupled system of equations furnishes a scale factor growth and energy density evolution that correctly reproduce the inflationary phase of the universe. After that, assuming a mechanism of energy transference to ordinary matter, the initial conditions generated after inflation drives the radiation-dominated phase and also the subsequent dark-matter evolution, since the Elko field is a good dark-matter candidate. The energy density of the field at the end of inflation, at the end of the radiation phase and for the present time are in agreement with the standard model estimates. The analysis was performed with a potential containing a quadratic mass term plus a quartic self-interaction term, which follows naturally from the theory of mass-dimension-one fermions. Inflation occurs when the field makes a kind of transition around the Planck mass scale. The number of e-foldings during inflation was found to be strongly dependent on the initial conditions of the Elko field, as occurs in chaotic inflationary models. An upper limit to the Elko mass is estimated. A possible interpretation of the inflation as a consequence of a kind of Pauli exclusion principle is presented at the end.